Ageism and perceptions of vulnerability: Framing of Age during the during the Covid-19 Pandemic - Schnell, Frauke; McConatha, Jasmin Tahmaseb; Magnarelli, Jaqueline; Broussard, Jordan (Advances in Social Sciences Research Journal, 2021)
Media representations of the Covid-19 pandemic and its devastating consequences have shaped people’s fears, anxiety, and perceptions of vulnerability. Social scientists have examined the consequences of how information is “framed.” Framing theory asserts that issues can be portrayed differently by emphasizing or de-emphasizing aspects and information. According to Lakoff (2004) the impact of a message is not based on what is said but how it is said. Theories of framing focus on how the media frames issues, which then structure and shape attitudes and policies. A news article serves as a frame for an intended message. This paper examines the ways that “age” has been framed during the Covid-19 pandemic. One of the most dominant frames in terms of COVID-19 coverage is how the pandemic has been analyzed through the lens of age and framed in terms of age discrimination. The results of news articles appearing in several prominent newspapers indicate that the perceptions of elders and their vulnerabilities to severe consequences from Covid-19 are likely to help perpetuate or create age discrimination.